Modified Atomic Orbital Calculations for $(1s,nl)^3L^{π}$ and $_2 (1,0)_n^{±1,3}S^e$ Excited States of He Isoelectronic Sequence (Journal of Atomic and Molecular Sciences, 2010)
The singly $(1s,ns)^{3}S^{e}$, $(1s,np)^{3}P^{o}$, $(1s,nd)^{3}D^{e}$ excited states and the doubly $_{2}(1,0)_{n}^{+1}S^{e}$ and $_{2}(1,0)_{n}^{-3}S^{e}$ $(n≤10)$ autoionizing states of the helium isoelectronic sequence are investigated using Modified Atomic Orbital Theory (MAOT). Total energies up to $Z = 10$ and excitation energies with $Z = 2$~$5$ are presented and comparison with experimental and theoretical available results indicates a good agreement. In addition, the method is applied in the calculation of accurate results in very high $Z$ - He isoelectronic sequence with $11≤ Z≤58$ and with $Z = 60,$ 70, 80, 90 and 92 for the $(1s,ns)^{1,3}S^{e}$, $(1s,np)^{1,3}P^{o}$, $(1s,nd)^{1,3}D^{e}$, $_{2}(1,0)_{n}^{+1}S^{e}$ and $_{2}(1,0)_{n}^{-3}S^{e}$ $(n≤7)$ excited states. The results obtained for these high $Z$ - He isoelectronic sequence are in good agreement with double sums over the complete hydrogen spectrum calculations Ivanov and Safronova.